Machinima interventions: innovative approaches to immersive virtual world curriculum integration - Andrew John Middleton; Richard Mather (Association for Learning Technology, 2008)
The educational value of Immersive Virtual Worlds (IVWs) seems to be in their social immersive qualities and as an accessible simulation technology. In contrast to these synchronous applications this paper discusses the use of educational machinima developed in IVW virtual film sets. It also introduces the concept of media intervention, proposing that digital media works best when simply developed for deployment within a blended curriculum to inform learning activity, and where the media are specifically designed to set challenges, seed ideas, or illustrate problems. Machinima, digital films created in IVWs, or digital games offer a rich mechanism for delivering such interventions. Scenes are storyboarded, constructed, shot and edited using techniques similar to professional film production, drawing upon a cast of virtual world avatars controlled through a human–computer interface, rather than showing real-life actors. The approach enables academics or students to make films using screen capture software and desktop editing tools. In student-generated production models the learning value may be found in the production process itself. This paper discusses six case studies and several themes from research on ideas for educational machinima including: access to production; creativity in teaching and learning; media intervention methodology; production models; reusability; visualisation and simulation.